Let's bake bread! : a family cookbook to foster learning, curiosity, and skill building in your kids - Ohara, Bonnie (Artisan, 2023)
"In the long-awaited follow-up to her first book Bread Baking for Beginners (more than 130,000 copies sold), baker Bonnie Ohara offers the ultimate guide for baking with your kids, with a delicious array of kid-friendly recipes and extracurricular lessons on history, seasonality, culture, and more. In Let's Bake Bread!, Bonnie Ohara draws on her expertise as a professional baker and homeschooling mother of three children to teach parents how to turn baking bread into an activity for the whole family, with kid-friendly recipes and teachable moments throughout. Organized into chapters geared towards specific age groups, ranging from ages 3 to 16+, each section presents age-appropriate recipes and lessons to explore while practicing the art of bread baking-all with delicious results. Recipes for Fluffy Milk Bread and Sweet Dreams Bunny Bread are made with forgiving, enriched doughs that allow for sensory play for little ones; middle-aged kids can make a Summer Focaccia or a Winter Squash Fougasse and explore themes of seasonality and food systems; recipes geared towards pre-teens focus on breads from the globe, including Naan and Cider Barm Bread; and older kids or skilled bakers can learn the science of sourdough, with recipes for a Simple Tin Loaf and a Sprouted Quinoa Chia Bread. Annotations throughout the recipes give cues for parents to keep their children engaged and curious and lend pointers for taking bread baking skills to the next level, plus suggestions for additional activities and reading to continue the fun even after baking is done"--